Pre-study feasibility and identifying sensitivity analyses for protocol pre-specification in comparative effectiveness research. (May 2014) - Girman, Cynthia J; Faries, Douglas; Ryan, Patrick; Rotelli, Matt; Belger, Mark; Binkowitz, Bruce; O'Neill, Robert; ,
The use of healthcare databases for comparative effectiveness research (CER) is increasing exponentially despite its challenges. Researchers must understand their data source and whether outcomes, exposures and confounding factors are captured sufficiently to address the research question. They must also assess whether bias and confounding can be adequately minimized. Many study design characteristics may impact on the results; however, minimal if any sensitivity analyses are typically conducted, and those performed are post hoc . We propose pre-study steps for CER feasibility assessment and to identify sensitivity analyses that might be most important to pre-specify to help ensure that CER produces valid interpretable results.